PENGARUH PROFITABILITAS, LIKUIDITAS, DAN LEVERAGE TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN - Wahyudin, Wahyudin; Su'un, Muhammad; Nur, Andi Nirwana (Oikos Nomos: Jurnal Kajian Ekonomi dan Bisnis, 2024)
This study investigates the impact of profitability, liquidity, and leverage on stock returns within food and beverage manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2022. The secondary data was derived from annual financial reports of food and beverage manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2022, sourced from the Indonesia Stock Exchange website www.idx.co.id. Sampling utilized a purposive technique based on specific criteria, resulting in a sample of 272 from 84 food and beverage manufacturing companies listed on the Indonesia Stock Exchange during the period of 2019-2022. The study utilized 70 observation data points from 39 companies, along with 202 issued data points that met specific criteria. The employed analysis method is multiple linear regression analysis. The results demonstrate that the profitability ratio, as assessed by the Return on Equity (ROE), shows a partial effect, while the liquidity ratio, indicated by the Current Ratio (CR), does not significantly influence stock returns. In contrast, the leverage ratio, measured by the Debt-to-Equity Ratio (DER), exhibits a positive and significant impact on stock returns. The profitability ratio, as indicated by the Return on Equity (ROE), the liquidity ratio, measured by the Current Ratio (CR), and the leverage ratio, represented by the Debt-to-Equity Ratio (DER), all exhibit a positive and significant impact on stock returns.